An Analysis of Inflectional and Derivational Affixes on Psalms Chapters 1-10 From the Bible King James Version - Samosir, Nelly Elisabeth; Pasaribu, Rotua Elfrida; Sembiring, Rony Arahta (Fakultas Sastra - Universitas Muslim Indonesia, 2023)
The objective of this study is to identify the inflectional and derivational affixes present in Psalms chapters 1-10 of the King James Version, and to examine the manner in which these affixes are processed. This study employs a qualitative research approach characterized by a descriptive design. When examining the data, the author emphasizes the inflectional and derivational affixes found in the King James translation of the Bible, as outlined by Katamba's theory (1993:40) that states